Mesoscale material fatigue test sample preparation method based on femtosecond laser ablation

The preparation of mesoscopic laser ablation technology is used to prepare fatigue test samples of mesoscopic materials, which solves the problems of complex, time-consuming and cost-effective preparation of fatigue test samples in the prior art, and realizes efficient and low-cost preparation of fatigue test samples. It is suitable for precious metals and ceramic materials, avoids stress concentration and heat diffusion, and improves processing efficiency and accuracy.

CN120507186APending Publication Date: 2025-08-19NANJING UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510587264.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-08
Publication Date
2025-08-19

AI Technical Summary

Technical Problem

The existing preparation methods for fatigue testing samples of small-scale materials are complex, time-consuming, costly and potential processing defects, making it difficult to meet the preparation requirements of mesoscopic fatigue testing samples, especially when loading the tension cycle, stress concentration and surface damage cannot be avoided.

Method used

Femtosecond laser ablation technology is used to prepare mesoscopic material fatigue test samples through preparation, polishing and cutting steps, including mechanical thinning, polishing and femtosecond laser cutting, combined with arc gauge segment design to avoid stress concentration, and polishing to remove the damaged layer by reducing laser power and increasing pulse density.

Benefits of technology

It realizes efficient and low-cost mesoscale material fatigue test sample preparation, avoids heat diffusion and stress concentration, ensures that the sample surface is flat, is suitable for fatigue testing of precious metals and ceramics, and improves processing efficiency and accuracy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120507186A_ABST
    Figure CN120507186A_ABST
Patent Text Reader

Abstract

The invention relates to a method for preparing a mesoscale material fatigue test sample based on femtosecond laser ablation. The method specifically comprises the following steps: preparing a first strip sheet sample; carrying out mechanical thinning on the first long-strip sheet sample to obtain a second long-strip sheet sample; polishing the second long-strip sheet sample to obtain a third long-strip sheet sample without a mechanical damage layer on the surface; fixing the third strip-shaped sheet sample on a glass sheet, and cutting arc gauge length sections on two sides of the middle part of the third strip-shaped sheet by using femtosecond laser to obtain an arc-shaped preliminary fatigue test sample; the power of the femtosecond laser is reduced to 15-30% of the cutting power, the pulse density is improved by 100%, the side face of the arc gauge length section of the arc-shaped preliminary fatigue test sample is polished, and the fatigue test sample is obtained. According to the invention, the test sample with a small volume can be obtained, the processing efficiency is high, the cutting surface damage layer can be ignored, and the method is suitable for different materials such as metals, ceramics and polymers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of material fatigue test sample preparation, and in particular relates to a method for preparing a mesoscale material fatigue test sample based on femtosecond laser ablation. Background Art

[0002] The use of micro-sized test samples to characterize the mechanical properties of materials is of great significance and has received increasing attention in recent years. When the available sample volume is limited, micro-scale mechanical testing is the only feasible way to evaluate mechanical properties. For example, the mechanical characterization of nuclear irradiated materials urgently needs to reduce the sample size to reduce radioactivity and save valuable experimental space; the mechanical testing of precious metal materials (such as gold, platinum, etc.) also needs to reduce the research cost by reducing the sample size; the existing new nanostructured materials can only obtain a limited volume of samples for mechanical testing and research due to preparation process limitations. In addition, micro-sized samples can also be used to test the mechanical testing of local areas of interest (such as welds, sample surfaces) and establish a more accurate relationship between material structure and performance.

[0003] Currently, common micro-scale mechanical tests mainly include micro-tensile tests, micro-column compression tests, micro-shear tests, and micro-cantilever bending tests. These testing techniques can usually only carry out monotonic loading tests and cannot be used for fatigue tests of tension-compression cyclic loading. In addition, common micro-scale mechanical tests usually use focused ion beam micro-nano processing equipment to prepare test samples. However, although the focused ion beam has high processing accuracy, it has low preparation efficiency and high cost, so it is only suitable for processing samples with a size of less than 10 microns. A large number of studies have shown that when the sample size is close to or smaller than the microstructure size (such as grain size), the mechanical behavior of the micro-sample deviates from the macroscopic sample, showing a significant sample size effect. Obtaining mechanical properties close to those of bulk materials, especially fatigue properties, has more important scientific and engineering significance, because the data can be directly used in scientific research and new material development, or guide engineering design and application.

[0004] In order to use microscale testing to study the fatigue behavior of bulk materials, it is necessary to increase the size of microscale specimens so that the samples contain enough grains or other microstructural information. At the same time, fatigue testing requires that the sample surface is flat, without surface undulations or stress concentration locations such as microcracks, and the sample surface cannot have defects such as processing damage layers that change the fatigue properties of the material. Currently available processing technologies or processes are difficult to meet the preparation requirements of microscale fatigue test samples. Conventional electric spark wire cutting or machining equipment can process sizes far exceeding 1mm, the size of the sample that can be processed is not small enough, and there is an obvious surface damage layer. Focused ion beam processing can process micron-level or even submicron-level samples, but the processing efficiency is low, and it is impossible to prepare samples of 10 microns and hundreds of microns. In addition, there is a problem of Ga+ injection on the sample surface, which may change the material properties. It is an urgent problem to process mesoscale test samples with a sample size greater than 10 microns and less than 1 mm to meet the requirements of tensile-compressive symmetrical fatigue or tensile-tensile fatigue testing. Summary of the Invention

[0005] The purpose of the present invention is to provide a method for preparing mesoscale material fatigue test samples based on femtosecond laser ablation, which is used to solve the problems of complex, time-consuming, high-cost and potential processing defects in the preparation process of micro-scale fatigue test samples.

[0006] The technical solution to achieve the purpose of the present invention is: a method for preparing mesoscale material fatigue test samples based on femtosecond laser ablation, comprising the following steps:

[0007] Step (1): preparing a first long thin slice sample;

[0008] Step (2): mechanically thinning the first long thin slice sample to obtain a second long thin slice sample;

[0009] Step (3): polishing the second long thin slice sample to obtain a third long thin slice sample with no mechanical damage layer on the surface;

[0010] Step (4): fix the third long thin slice sample on a glass sheet, and use a femtosecond laser to cut arc gauge segments on both sides of the middle of the third long thin slice to obtain an arc-shaped preliminary fatigue test sample;

[0011] Step (5): reducing the power of the femtosecond laser to 15-30% of the cutting power in step (4) and increasing the pulse density by 100%, polishing the side of the arc gauge section of the arc-shaped preliminary fatigue test sample to obtain a fatigue test sample;

[0012] Step (6): Clean the arc fatigue test sample.

[0013] Furthermore, the material of the sample is copper or copper alloy.

[0014] Furthermore, step (1) is specifically as follows: using an electric spark wire cutting machine, a diamond saw or a diamond wire cutting machine to cut out a first long thin slice sample from a thin plate sample with a thickness of less than 1 mm, and the thickness of the first long thin slice sample exceeds 500 μm.

[0015] Furthermore, step (2) is specifically as follows: ultrasonically cleaning the first long thin slice sample with clean water and ethanol in sequence; coarsely grinding the cleaned sample with sandpaper; fixing one side of the coarsely ground sample to a grinder with metal glue; fine-grinding the sample fixed on the grinder with sandpaper; placing the grinder with the finely ground sample fixed thereon in acetone for ultrasonic vibration to obtain a second long thin slice sample with a thickness between 10 μm and 500 μm.

[0016] Furthermore, step (3) is specifically as follows: using SiO2 suspension to vibrate and polish for 5-8 hours to remove scratches and stress layers on the surface, and ensuring that both sides of the sample are parallel.

[0017] Furthermore, step (4) is specifically as follows: covering the two ends of the sample with two clean pieces of paper, and fixing the paper pieces on the glass sheet with tape, thereby fixing the sample; setting the femtosecond laser parameters as follows: wavelength less than 515nm, laser pulse width less than 500fs, power less than 5W, laser repetition frequency between 100 and 1000KHz, using a displacement platform to control the laser cutting path, and using the displacement platform position to control the adjacent points of laser emission to have 70% to 95% laser spot overlap; the ratio of the width and thickness of the minimum part of the obtained arc-shaped preliminary fatigue test sample to the average grain size is greater than 10.

[0018] Furthermore, step (5) is specifically as follows: reducing the laser processing power to 20-30% of the cutting power, and increasing the pulse density to 10,000, the laser cutting track is retracted by 0.5 to 2 microns every n passes, where 3≤n≤7, and the total retracted thickness of the track during the polishing process needs to be more than 5 microns, completely removing the laser ablation damage layer introduced during the laser cutting process in step (4), and at the same time not introducing a new laser ablation damage layer.

[0019] Furthermore, step (6) is specifically as follows: using a dust collector to remove residual ion precipitation from the surface of the sample of step (5), and then ultrasonically cleaning it with clean water, anhydrous ethanol, and isopropanol in sequence to obtain a micron-scale sample that can be used for tensile and compressive fatigue at the mesoscopic scale.

[0020] A mesoscopic material fatigue test sample is prepared by the above method.

[0021] Compared with the prior art, the present invention has the following significant advantages:

[0022] 1. The femtosecond laser pulse time used in the present invention is significantly shorter than the thermal oscillation period of the crystal lattice of various materials, which can effectively limit the heat diffusion during the cutting process, reduce the heat-affected zone, and achieve true "cold processing". The femtosecond laser-based technical solution of the present invention is suitable for low-cycle fatigue testing of relatively precious tiny sample thin materials, and the design of the arc gauge section effectively avoids stress concentration during the fatigue process.

[0023] 2. The present invention ensures that both sides of the sheet sample are completely parallel through vibration polishing, so that it can meet the centering requirement during the compression process and ensure that the sample will not warp during the compression stage.

[0024] 3. Compared with traditional focused ion beam micromachining technology, the technical solution of the present invention has the advantages of high processing efficiency, short processing time and low processing cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is the laser loading path diagram of Example 1 of the present invention.

[0026] Figure 2 This is the laser loading path diagram of comparative example 1 of the present invention.

[0027] Figure 3 This is the sample morphology of Example 1 of the present invention.

[0028] Figure 4 This is the sample morphology of Comparative Example 1 of the present invention.

[0029] Figure 5 This is a cross-sectional schematic diagram of Example 1 of the present invention taken by laser confocal microscopy.

[0030] Figure 6 This is a test result diagram of Example 1 of the present invention.

[0031] Figure 7 This is a test result diagram of Comparative Example 1 of the present invention.

[0032] Figure 8 This is the SEM morphology of Example 1 of the present invention after the fatigue test.

[0033] Figure 9 This is the SEM morphology of comparative example 1 of the present invention after the fatigue test. DETAILED DESCRIPTION

[0034] The present invention is further described in detail below with reference to the accompanying drawings.

[0035] Example 1

[0036] Step 1: Use a disk saw to cut a cold-rolled copper sheet with a thickness of 500 μm along the TD direction into copper strips with a width of 5 mm in the RD direction. Use a disk saw to cut the obtained copper strips along the RD direction to obtain thin slices of 5*0.5*1 mm. The cut samples are ultrasonically cleaned with clean water and ethanol.

[0037] Step 2: Use #800, #1200, #2000, and #4000 sandpaper for rough grinding. Attach the rough-ground side to the grinder with metal glue. Then use #800, #1200, #2000, and #4000 sandpaper for fine grinding. Place the grinder with the sample in acetone and ultrasonically vibrate. Remove the polished sample. The thinned copper sheet should have a size of 5*0.5*0.15mm.

[0038] Step 3: The sample obtained in step 2 was vibrated and polished using a SiO2 suspension for 6 hours to remove surface scratches and stress layers, and to ensure that both sides of the thin slice sample were parallel to obtain a surface that could be observed under a scanning electron microscope;

[0039] Step 4: Place the sample obtained in step 3 flat on a glass slide, cover both ends of the sample with two clean paper sheets, and use tape to fix the paper sheets to the glass slide to fix the sample on the glass slide and facilitate removal of the sample after femtosecond laser cutting.

[0040] Step 5: Turn on the femtosecond laser processing equipment. The initial processing power of the femtosecond laser is d / 0.04W, where d is the sample thickness in mm. The calculated result is rounded up and does not exceed 5W. Import the laser path and start laser processing of the arc gauge segment. The laser processing path is as follows: Figure 1 As shown;

[0041] Step 6: Reduce the laser processing power to 20-30% of the cutting power and increase the pulse density to 10,000 to complete the laser polishing of the cut section;

[0042] Step 7: Take the sample processed by femtosecond laser in step 5, use a dust collector to remove the residual ion precipitation on the surface, and use clean water, anhydrous ethanol, and isopropanol to perform ultrasonic cleaning in sequence, so as to obtain a micron-scale sample that can be used for tensile and compressive fatigue at the mesoscopic scale. The obtained sample is as follows: Figure 3 shown.

[0043] Comparative Example 1

[0044] Step 1: Use a disk saw to cut a cold-rolled copper sheet with a thickness of 500 μm along the TD direction into copper strips with a width of 5 mm in the RD direction. Use a disk saw to cut the obtained copper strips along the RD direction to obtain thin slices of 5*0.5*1 mm. The cut samples are ultrasonically cleaned with clean water and ethanol.

[0045] Step 2: Polish with #800, #1200, #2000, and #4000 sandpaper in sequence. Attach the polished side to the metal adhesive and thin the sample to 150-200μm. Then, fine-grind with #800, #1200, #2000, and #4000 sandpaper in sequence. Place the grinder in acetone for ultrasonic vibration and remove the polished sample. The thinned copper sheet should be 5*0.5*0.15mm in size.

[0046] Step 3: The sample obtained in step 2 was vibrated and polished using a SiO2 suspension for 6 hours to remove surface scratches and stress layers, and to ensure that both sides of the thin slice sample were parallel to obtain a surface that could be observed under a scanning electron microscope;

[0047] Step 4: Place the sample obtained in step 3 flat on a glass slide, cover both ends of the sample with two clean paper sheets, and use tape to fix the paper sheets to the glass slide to fix the sample on the glass slide and facilitate removal of the sample after femtosecond laser cutting.

[0048] Step 5: Turn on the femtosecond laser processing equipment. The initial processing power of the femtosecond laser is d / 0.04W, where d is the sample thickness in mm. The calculated result is rounded up and does not exceed 5W. Import the laser path and start laser processing of the dog-bone gauge segment. The laser processing path is as follows: Figure 2 As shown;

[0049] Step 6: Reduce the laser processing power to 20-30% of the cutting power and increase the pulse density to 10,000 to complete the laser polishing of the cut section;

[0050] Step 7: Take the sample processed by femtosecond laser in step 5, use a dust collector to remove the residual ion precipitation on the surface, and use clean water, anhydrous ethanol, and isopropanol to perform ultrasonic cleaning in sequence, so as to obtain a micron-scale sample that can be used for tensile and compressive fatigue at the mesoscopic scale. The obtained sample is as follows: Figure 4 shown.

[0051] After the sample preparation of Example 1 was completed, the roughness of the femtosecond laser processed surface was analyzed by laser confocal analysis. Figure 5 The line roughness of Example 1 is 4.3 μm. The examples and comparative examples were subjected to tension and compression low cycle fatigue tests, and the test results are shown in the figure below. Figure 6 and 7 After the fatigue test, the surface of the embodiment and the comparative example was analyzed by SEM, as shown in FIG. Figure 8 and 9As shown in the figure, the crack initiation of the dog-bone sample is affected by stress concentration, and fatigue cracks are initiated at both corners; the arc gauge section is less affected by stress concentration.

[0052] The tensile-compression fatigue tensile sample preparation method based on the femtosecond laser processing system adopted in the present invention can well solve the defects of the existing sample preparation method. The pulse time of the femtosecond laser is in the order of femtoseconds, 1fs=10 -15 s. In such a short period of time, the laser pulse time is much shorter than the relaxation time of the excited electrons in the material, which effectively limits the heat diffusion during the processing, thereby achieving the "cold processing" we need, effectively avoiding the transformation of the sample due to heating, and also ensuring the accuracy of the cutting size. Secondly, by designing the arc gauge segment, it is possible to effectively avoid stress concentration at the corners during the fatigue process, which causes cracks to preferentially extend at the corners. The femtosecond laser processing system is used to prepare micron-scale (10μm to 500μm) samples. Due to the small size of the samples, it is convenient to perform subsequent SEM, TEM and other equipment characterization of the fatigued samples. Moreover, the femtosecond laser processing takes a very short time, generally only 5 to 15 minutes per sample, and the prepared micron-scale tensile samples contain a large number of grains, so the experimental result errors caused by the size effect can be avoided.

Claims

1. A method for preparing mesoscopic material fatigue test samples based on femtosecond laser ablation, characterized in that: The steps include: Step (1): preparing a first long thin slice sample; Step (2): mechanically thinning the first long thin slice sample to obtain a second long thin slice sample; Step (3): polishing the second long thin slice sample to obtain a third long thin slice sample with no mechanical damage layer on the surface; Step (4): fix the third long thin slice sample on a glass sheet, and use a femtosecond laser to cut arc gauge segments on both sides of the middle of the third long thin slice to obtain an arc-shaped preliminary fatigue test sample; Step (5): reducing the power of the femtosecond laser to 15-30% of the cutting power in step (4) and increasing the pulse density by 100%, polishing the side of the arc gauge section of the arc-shaped preliminary fatigue test sample to obtain a fatigue test sample; Step (6): Clean the arc fatigue test sample.

2. The method according to claim 1, characterized in that The material of the sample is copper or copper alloy.

3. The method according to claim 2, characterized in that Step (1) specifically comprises: using an electric spark wire cutting machine, a diamond saw or a diamond wire cutting machine to cut out a first long thin slice sample from a thin plate sample with a thickness of less than 1 mm, wherein the thickness of the first long thin slice sample exceeds 500 μm.

4. The method according to claim 3, characterized in that Step (2) is specifically as follows: ultrasonically cleaning the first long thin slice sample with clean water and ethanol in sequence; coarsely grinding the cleaned sample with sandpaper; fixing one side of the coarsely ground sample to a grinder with metal glue; fine-grinding the sample fixed on the grinder with sandpaper; placing the grinder with the finely ground sample fixed thereon in acetone for ultrasonic vibration to obtain a second long thin slice sample with a thickness between 10 μm and 500 μm.

5. The method according to claim 4, characterized in that Step (3) is specifically as follows: using SiO2 suspension to vibrate and polish for 5-8 hours to remove scratches and stress layers on the surface, and ensuring that both sides of the sample are parallel.

6. The method according to claim 5, characterized in that Step (4) is specifically as follows: covering the two ends of the sample with two clean pieces of paper, and fixing the paper pieces on the glass sheet with tape, thereby fixing the sample; setting the femtosecond laser parameters as follows: wavelength less than 515nm, laser pulse width less than 500fs, power less than 5W, laser repetition frequency between 100 and 1000KHz, using a displacement platform to control the laser cutting path, and using the displacement platform position to control the laser emission of adjacent points so that there is 70% to 95% overlap of laser spots; the ratio of the width and thickness of the smallest part of the obtained arc-shaped preliminary fatigue test sample to the average grain size exceeds 10.

7. The method according to claim 6, characterized in that Step (5) is specifically as follows: reducing the laser processing power to 20-30% of the cutting power, and increasing the pulse density to 10,000, shrinking the laser cutting track by 0.5 to 2 microns every n passes, where 3≤n≤7, and the total shrinkage thickness of the track during the polishing process must exceed 5 microns, completely removing the laser ablation damage layer introduced during the laser cutting process in step (4), and at the same time not introducing a new laser ablation damage layer.

8. The method according to claim 7, characterized in that Step (6) is specifically as follows: using a dust collector to remove residual ion precipitation from the surface of the sample of step (5), and then ultrasonically cleaning it with clean water, anhydrous ethanol, and isopropanol in sequence to obtain a micron-scale sample that can be used for tensile and compressive fatigue at the mesoscopic scale.

9. A mesoscopic material fatigue test sample, characterized in that: The method according to any one of claims 1 to 8 is used for preparation.